Rearrangement of 2-Quinolyl- and 1-Isoquinolylcarbenes to Naphthylnitrenes - Lân, Nguyen Mong; Burgard, Riko; Wentrup, Curt (Journal of organic chemistry, 2004)
2-Quinolylcarbene 23 and 1-isoquinolylcarbene 33 are generated by flash vacuum thermolysis (FVT) of the corresponding triazolo[1,5-a]quinoline and triazolo[5,1-a]isoquinoline 19 and 29, as well as 2-(5-tetrazolyl)quinoline and 1-(5-tetrazolyl)isoquinoline 20 and 30, respectively. These carbenes rearrange to 1- and 2-naphthylnitrene 21 and 31, respectively, and the nitrenes are also generated by FVT of 1- and 2-naphthyl azides 18 and 28. The products of FVT of both the nitrene and carbene precursors are the 2- and 3-cyanoindenes 26 and 27 together with the nitrene dimers, viz. azonaphthalenes 25 and 35, and the H-abstraction products, aminonaphthalenes 24 and 34. All the azide, triazole, and tetrazole precursors yield 3-cyanoindene 26 as the principal ring contraction product under conditions of low FVT temperature (340−400 °C) and high pressure (1 Torr N2 as carrier gas for the purpose of collisional deactivation). This ring contraction reaction is strongly subject to chemical activation, which caused extensive isomerization of 3-cyanoindene to 2-cyanoindene under conditions of low pressure (10-3 Torr). 2-Cyanoindene is calculated to be ca. 1.7 kcal/mol below 3-cyanoindene in energy; accordingly, high-temperature FVT of these cyanoindenes always gives mixtures of the two compounds with the 2-cyano isomer dominating. Photolysis of trizolo[1,5-a]quinoline 19 and triazolo[5,1-a]isoquinoline 29 in Ar matrixes causes partial ring opening to the corresponding 2-diazomethylquinoline 19‘ and 1-diazomethylisoquinoline 29‘. The photolysis of the former gives rise to a small amount of the cyclic ketenimine 22, the intermediate connecting 2-quinolylcarbene and 1-naphthylnitrene.